Assessing Students' Object-Oriented Programming Skills with Java: The "Department-Employee" Project - Zhang, Xihui; Crabtree, John D.; Terwilliger, Mark G.; Redman, Tyler T. (The Journal of computer information systems, 2020)
Java is arguably today's most popular and widely used object-oriented programming language. Learning Java is a daunting task for students, and teaching it is a challenging undertaking for instructors. To assess students' object-oriented programming skills with Java, we developed the "Department-Employee" project. In this article, we review the history of object-oriented programming, provide an overview of object-oriented programming with Java, and present a summary of existing Java projects and their limitations. We also provide the project specifications as well as the course background, grading rubric, and score reports. Survey data are presented on students' backgrounds, as well as students' perceptions regarding the project. Results from the instructor score reports, correlation of the project score and the final course score, and student perceptions show that the "Department-Employee" project is effective in assessing students' object-oriented programming skills with Java.